2022
DOI: 10.3390/molecules27134297
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Inhibitors of Monoamine Oxidases—Potential New Drug Leads for Neuroprotection, Neurological Disorders, and Neuroblastoma

Abstract: Monoamine oxidase inhibitors (MAOIs) are an important class of drugs prescribed for treatment of depression and other neurological disorders. Evidence has suggested that patients with atypical depression preferentially respond to natural product MAOIs. This review presents a comprehensive survey of the natural products, predominantly from plant sources, as potential new MAOI drug leads. The psychoactive properties of several traditionally used plants and herbal formulations were attributed to their MAOI consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 210 publications
1
33
0
Order By: Relevance
“…In addition, some natural products from plant sources with reversible MAO inhibitory properties have been identified and are being tested in different pathological contexts. For example, some alkaloids act as potent MAO-A inhibitors and may provide beneficial effects on neuroblastoma and other cancer cell lines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some natural products from plant sources with reversible MAO inhibitory properties have been identified and are being tested in different pathological contexts. For example, some alkaloids act as potent MAO-A inhibitors and may provide beneficial effects on neuroblastoma and other cancer cell lines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the function of the mitochondrial complex I under the control of monoamine oxidase, MPTP is a lipophilic neurotoxin that easily crosses the blood-brain barrier and causes degenerative necrosis of DA neurons [ 29 ]. Coincidentally, curcumin inhibits monoamine oxidase B and protects DA neurons [ 17 ]. Our data showed that different doses of curcumin improved DA neuron morphology and number, mitochondrial structure, and neuronal vacuolar degeneration, with higher doses being more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a polyphenol extracted from the rhizomes of Curcuma longa , is converted into biologically active metabolites in the intestine by microbial digestion [ 13 ]. Nowadays, it has been shown to have multiple effects such as anti-inflammatory [ 14 ], antioxidant [ 15 ], anticancer [ 16 ], and mitochondrial protection [ 17 ]. The bidirectional interplay between curcumin and gut microbes has been demonstrated, as curcumin is not only metabolized by the enzymes of the gut microbes to produce active metabolites but it also strengthens the intestinal barrier and changes the composition of the gut microbes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monoamine oxidase (MAO) and cholinesterase (ChE) play important roles in the regulation of nerve conduction by catalyzing the degradation of neurotransmitters. Along with abnormal protein aggregation, low neurotransmitter levels are associated withneuron death [ 1 , 2 , 3 ]. Alzheimer’s disease (AD) is a common neurodegenerative diseasecharacterized by low levels of the neurotransmitters acetylcholine (ACh) and butyrylcholine (BCh), both of which are involved in cognition.…”
Section: Introductionmentioning
confidence: 99%